The Never Girls. Volume 2, books 4-6 - Thorpe, Kiki (Disney the Never girls, 2016)
In three stories, Kate is approached by a herd of mist horses, Gabby is the flower girl in a wedding, and Lainey discovers the hideout of the Lost Boys in the woods.